1983
DOI: 10.1152/ajprenal.1983.245.3.f303
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of epinephrine on renal potassium secretion: a micropuncture study

Abstract: The effect of epinephrine on renal potassium excretion was examined in the rat. In group I KCl was infused acutely to increase plasma K (PK) by 2.0 meq/liter; urinary K excretion (UKV) rose by 1.22 mueq/min. In group II rats, which received a similar dose of KCl but with epinephrine, the increase in PK (delta = 0.8 meq/liter, P less than 0.001) was blunted and UKV was reduced (delta = 0.23 mueq/min, P less than 0.001). To determine whether the reduction in UKV resulted from the smaller increase in PK or from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…11 Hypokalemia may also occur due to active inhibition of potassium secretion in the cortical collecting tubule, possibly caused by stimulation of membrane sodium potassium-dependent adenosine triphosphatase that results in hyperpolarization of the cellular membrane potential. 36 For chronic asthma, there was no previous study to evaluate the prevalence of hypokalemia in patients with chronic asthma receiving inhaled steroids and ␤ 2 -agonists. Although hypokalemia was only found in small number of our asthmatic patients (5.4%), the therapeutic drugs administered for the management of chronic asthma were found to have no effect on the serum potassium level.…”
Section: Discussionmentioning
confidence: 99%
“…11 Hypokalemia may also occur due to active inhibition of potassium secretion in the cortical collecting tubule, possibly caused by stimulation of membrane sodium potassium-dependent adenosine triphosphatase that results in hyperpolarization of the cellular membrane potential. 36 For chronic asthma, there was no previous study to evaluate the prevalence of hypokalemia in patients with chronic asthma receiving inhaled steroids and ␤ 2 -agonists. Although hypokalemia was only found in small number of our asthmatic patients (5.4%), the therapeutic drugs administered for the management of chronic asthma were found to have no effect on the serum potassium level.…”
Section: Discussionmentioning
confidence: 99%
“…Vasopressin has a stimulatory effect on renal potassium secretion, mediated by an initial increase in apical sodium permeability that leads to membrane depolarization and increased potassium secretion [38]. Insulin and epinephrine inhibit renal potassium secretion [40,41]. Insulin and epinephrine inhibit renal potassium secretion [40,41].…”
Section: Renal Handling Of Potassiummentioning
confidence: 99%
“…Earlier studies also found decreased serum potassium levels to be the earliest form of electrolyte disturbance in asthma, and it was related to the use of β2-agonists. 7 Mildly decreased serum potassium levels have also been reported in untreated patients with severe asthma due to the stress of the asthmatic attacks.…”
Section: Discussionmentioning
confidence: 99%